Nodulation and nitrogen fixation on vegetative soybean plants as affected by photoperiod and gibberellic acid - Balatti, Pedro Alberto (1990)
Long-day photoperiods and applications of gibberellic acid promoted shoot growth by stimulating leaf enlargement as a result of increasing avaliable photosynthates, which was also reflected in the higher leaf, stem and nodule plant dry weights. Short-day plants had more nodules, but they were smaller (by weight) than those of long-day plants. Gibberellic acid at 1.5×10−6 M enhanced nodule growth without preventing nodule formation. Factors other than just gibberellic acid are concluded to be involved in the responses of nodulation and nitrogen fixation to day length.